Model Relasi Islam-Kristen pada Masa Nabi: Sebuah Tinjauan Historis - Akhmad Siddiq (Jurnal Penelitian Ilmu Ushuluddin, 2023)
Attempts to build inter-religious harmony obtained influential obstacles within social relationship that is regularly based on never-ending ideological discourses. Every religion comes with its own basic faith and claim of truth. Even though, this claim should not normatively exclude the faith of others. In other word, religious believers could not assert their own faith to blame other different faiths. This paper argues that inter-religious harmony, especially between Islam and Christianity, is not only based on doctrinal-ideological argument but also historical evidences. This research will portray the relations between Islam and Christianity in the era of the Prophet Mohammad that could be illustrated in three periods: (1) pre-revelation, (2) the period of Mecca, and (3) the period of Medina. The paper will also explain the Islam-Christian relation model in the era of the Prophet by using historical-critics and hermeneutical-phenomenology.